Implementasi Metode Drill and Practice dalam Meningkatkan Kemampuan Praktik Wudhu Santri TPQ - Hermansyah, David; Aqodiah; Khaeruddin Said (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
This research aims to investigate the implementation of the Drill and Practice method in enhancing the ablution (wudhu) practical skills of students at Taman Pendidikan Al-Qur'an (TPQ). The research design employed is quantitative with a pre-test and post-test approach. The instrument utilized consists of a set of 5 essay questions. The research subjects encompassed 17 TPQ students participating in the learning program utilizing the Drill and Practice method. The research findings indicate that the average pre-test score was 82.35, while the post-test score increased to 91.54. This signifies a significant improvement in ablution practical skills following the implementation of the Drill and Practice method. The N-Gain analysis yielded an average of 0.48 (moderate category) or 48.07% in percentage terms (moderately positive category). These findings affirm the effectiveness of the Drill and Practice method in enhancing the ablution practical skills of TPQ students. This research contributes to the understanding of instructional methods that can be implemented in the context of religious education. The practical implications of this study can serve as a reference for TPQ administrators and educators to enhance the quality of religious education, particularly in the daily practice of rituals such as ablution. Keywords: Drill and Practice Method; Religious Understanding; Religious Character; Ablution.